Additional recommended abbreviations for the names of genera of the phylum Tardigrada - Perry, Emma; Miller, William R.; Kaczmarek, Łukasz (Zootaxa, 2021)
Since we proposed the standardization of a three-letter abbreviation for the genera of the phylum Tardigrada (Perry et al. 2019) there have been 17 new genera and sub-genera described. In addition, we have been informed by colleagues using the three-letter abbreviations that some editors and reviewers have challenged the abbreviations as not meeting ICZN rules.